HAFIZ HUSNIJA-EF. SEMIĆ - Dautović, Ferid (Novi Muallim, 2021)
UDK 28:929 Semić H. Rad tematizira život i rad hafiza Husnija-ef. Semića, čuvenog visočkog alima koji je svojim djelovanjem obilježio rad Islamske zajednice u Visokom polovinom XX stoljeća. U radu su navedeni osnovni biografski podaci o Husnija-ef., te je predstavljen njegov imamsko-muallimski rad u Perutačkoj džamiji i organima Islamske zajednice u Visokom. Posebno je istaknut doprinos hafiza Semića razvoju hifza i formiranju Udruženja ilmijje u Bosni i Hercegovini. Summary This article relates about life and work of a well-known ‘alim of Visoko of the mid-20th century, hafiz Husnija-ef. Semić. His efforts and contribution marked the work of the Islamic Community of Visoko in that period. The article presents basic biographical data about effendi Husnija and his contribution as an imam and a mua’llim of Perutačka mosque as well as his work in other departments of the Islamic Community of Visoko. Extraordinary contribution of hafiz Semić to the development of hifz and his role in formation of ‘Ilmiyya Sociaty of Bosnia and Herzegovina, are especially emphasised here.